Evaluating the Use and Acceptance of eLearning for Tertiary Education among Senior High School Students - Calora, Patricia O.; Lleva, Yrelle Mae R. (International Journal on Open and Distance e-Learning, 2018)
This paper sought to determine senior high school students’ preconceived notions about eLearning, as well as their behavioral intention to pursue tertiary education online. Generally, it aimed to evaluate the use and acceptance of eLearning technologies among senior high school students in a private high school in Los Baños, Laguna. Stratified sampling was used to identify respondents from five K-12 strands – accountancy, business and management (ABM); science, technology, engineering and mathematics (STEM); humanities and social science (HUMSS); information and communication technology (ICT); and general academic strand (GAS). Grounded in the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2), 200 respondents were surveyed. The moderating effect of UTAUT variables on the respondents’ behavioral intention was examined through correlation and regression analysis. Results showed that majority of the respondents had a positive behavioral intention to pursue tertiary education through eLearning. Of the UTAUT constructs, only performance expectancy was found to be a significant predictor of behavioral intention. A weak association was observed between sex and social influence; as well as between age and hedonic motivation.